Hitch [videorecording (DVD)] - Tennant, Andy, 1955-; Smith, Will, 1968-; Mendes, Eva, 1974-; James, Kevin, 1965- (Sony Pictures Home Entertainment, 2005)
Hitch is New York City's greatest matchmaker. Love is his job and when Albert Brennaman wins the heart of gorgeous society heiress Allegra Cole, Albert has Hitch to thank. So when tabloid columist Sara Melas decides to uncover the secret behind the relationships unlikely success, she's shocked to discover that Alex Hitchens, the charming young man she's been dating, is the legendary date doctor himself. Exposed in a front-page scoop, it's now up to Alex to try and save Albert and Allegra's relationship as well as his own.